6ER-026 Perception of a peer-to-peer mentoring experience with european pharmacy students in a student-run free clinic. (March 2019) - Roca Melendres, MM; Clark, J; Buena Gutierrez, P
Abstract : Background: While peer-to-peer mentoring and assessment is encouraged at many academic institutions, very little information exists about the effectiveness of this model in improving learning in student-run free clinics. Moreover, there is no information available about the impact on pharmacy students' perceptions of integrating international pharmacy exchange students into a peer-to-peer programme. Information generated by this study may provide support for the use of European students in peer-to-peer mentoring models. Purpose: To investigate students' perceptions of involving European pharmacy students in a peer-to-peer teaching model in a student-run free clinic. Material and methods: Data was collected in a student-run free clinic. A model was created where P4 and 5th year European students served as preceptors. The P4 students interacted and counselled English-speaking patients, whereas the European students focused on the Spanish-speaking patients. The teaching method was a modified version of the Hunter Mastery Teaching Model. An electronic survey was given to P2, P3 and P4 students to assess clinical experiences with patients assigned to European peer students. Sixteen survey items were evaluated that included students' perceptions in performing patient counselling, interviewing, writing electronic notes in the medical record, teaching patients how to monitor their medical condition and interacting with the medical team. Participants were asked to rate their perception of confidence from assessment statements on a 5-point rating scale, ranging from 1 – 'Strongly disagree' to 5 – 'Strongly agree.' Results: The survey was presented to 43 eligible participants from August to October 2018. Thirty-two students completed the survey (74% response). Seventeen were P2, nine were P3 and six were P4 students. Sixty-one per cent of the responses strongly agreed that the presence of the European students improved their confidence when teaching and counselling Spanish-speaking patients using the peer-to-peer model. There was a strong correlation between confidence and teaching patients (r = 0.571, p=0.01) and confidence and patient counselling (r=0.4517, p=0.01). Conclusion: The presence of the European students in a peer-to-peer mentoring model may improve P2 and P3 students' perception of confidence in medication counselling and teaching of Spanish-speaking patients on how to monitor their medical conditions. References and/or acknowledgements: Thanks to all our student volunteers. No conflict of interest.